2020
DOI: 10.1038/s41598-020-74715-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking study of potential phytochemicals and their effects on the complex of SARS-CoV2 spike protein and human ACE2

Abstract: Angiotensin converting enzyme 2 (ACE2) (EC:3.4.17.23) is a transmembrane protein which is considered as a receptor for spike protein binding of novel coronavirus (SARS-CoV2). Since no specific medication is available to treat COVID-19, designing of new drug is important and essential. In this regard, in silico method plays an important role, as it is rapid and cost effective compared to the trial and error methods using experimental studies. Natural products are safe and easily available to treat coronavirus a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 48 publications
4
176
1
3
Order By: Relevance
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Ofmentioning
confidence: 99%
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Ofmentioning
confidence: 99%
“…However, certain essential oils like geranium and lemon strongly reduces expression of ACE-2 in epithelial cells that can subvert viral invasion ( Senthil Kumar et al, 2020 ). Molecular docking and molecular dynamics studies have revealed that, hesperidin can distort the bound structure of ACE2 and spike protein fragment that could have potential anti-SRAS-CoV-2 implication ( Basu et al, 2020 ). However, many structural, non-structural and accessory proteins of SARS-CoV-2 adopt multiples strategies to modulate cytosolic interactome and subsequent immune function ( Fig.…”
Section: Mechanism Of Immunotoxicity: Ops Versus Sars-cov-2mentioning
confidence: 99%
“…The conventional antiviral drug development paradigm assumes that one drug targets one viral protein [20]. In this regard, molecular docking computational simulations have been extensively performed to discover plant-based bioactive molecules for specific SARS-CoV-2 protein targets [21]. This approach has multiple drawbacks among which is the robustness of complex virus-host interaction networks to individual protein perturbations.…”
Section: Identification Of Dietary Constituents and Consequent Designmentioning
confidence: 99%